Revestimento de nanocompósitos baseados em nanocelulose, acrescidos de extrato de película de amendoim na fisiologia e qualidade da lima ácida Tahiti armazenada - Laureth, Jessica Cristina Urbanski (2016)
Edible coatings may assist improvement of quality and conservation of fruits. Polysaccharide polymers, such as starch, pectin and cellulose have been constantly used as base to form coatings, but their physical properties do not provide proper barrier to gas and water vapor diffusion. Cellulose nanocrystals, when incorporated to edible coatings may improve their barrier properties. The addition of a natural antioxidant to the coating may improve conservation capacity of fruit. Natural antioxidants have relative instability, which may limit its reducing properties. Nevertheless, including nanocrystals may aggregate higher stability to added antioxidant. Thus, the objective of this research was assessing the effect of polymeric coatings, along with cellulose nanocrystals and vegetable extract on the physiology of Persian lime. It consisted of two experiments, the first assessed the effect of pectin (PEC), starch (ST) and cellulose gum (CMC) polymers added to cellulose nanocrystals (CN). The second differed from the first due to the addition of peanut peel extract, chosen because it has higher rates of antioxidant activity by DPPH, ABTS and FRAP methods in comparison with extracts of Persian lime and Rangpur seeds. In both experiments the assessments occurred during nine storage days under 23 °C ± 2 °C. Ethylene, CO2, fresh mass loss, firmness and chlorophyll were assessed. In the second were included DPPH, ABTS and FRAP antioxidant activity analyses, as well as total phenolic composites and ascorbic acid. In the first experiment, coatings formed by CMC, PEC and ST pure polymers with their respective nanocomposites called NCMC, NPEC and NST were efficient to reduce ethylene production until first three storage days. Among tested treatments, NPEC nanocomposite (12.01 mg CO2 kg-1 h-1) was more efficient than PEC (14.93 mg CO2 kg-1 h-1) to inhibit CO2 diffusion. PEC polymer when reinforced by NC (NPEC) was the only coating to reduce fresh mass loss of Persian lime, and it was also more efficient than PEC pure polymer when it comes to retention of chlorophyll. All tested nanocomposites and pure polymers were similarly efficient to keep fruit s firmness. In the second experiment the combination of pectin, cellulose gum, nanocrystals and extract was responsible to present lower ethylene and CO2 production rates. All tested coatings slowed fresh mass and firmness loss of fruits, but pectin and cellulose gum active nanocomposite was the coating able to contribute to the lowest rate of fresh mass loss and to highest rate of fruit s firmness retention, but the addition of extract did not influence these results. The reinforcement with cellulose nanocrystals was able to retain antioxidant activity off added coatings, which consisted of peanut peel extract. This research showed that pectin coatings, based on nanocrystals and the coatings from polymeric combination of pectin and cellulose gum, along with peanut peel extract and nanocrystals, presented better barrier properties against gases and water vapor, based on physiologic and physicochemical indicators